The Hermeneutic Priority of Which Question? A Speech Act Clarification for Interlocutionary Acts - Dickman, Nathan Eric (Informal Logic)

(untitled) (Informal Logic, 2021)
An axiom of philosophical hermeneutics is that questioning has hermeneutic priority. Yet there are many different kinds of questions. Which sort has priority in understanding complete thoughts and for bringing about a fusion of horizons? Speech act theory is one resource for specifying which kind. I first develop the broad notion of questioning in philosophical hermeneutics. Second, I examine aspects of question taxonomies in pedagogy as well as their shortcomings. Third, I turn to the Speech Act approach to questioning and provide a challenge to this theory for adequately addressing what kind takes hermeneutic priority. I propose the category of “suspensives” as the kind of interlocutionary act definitive for questions that have hermeneutic priority.